A generalizable TCAD framework for silicon FinFET spin qubit devices with electrical control. (February 2023) - Ding, Qian; Kuhlmann, Andreas V.; Fuhrer, Andreas; Schenk, Andreas
Abstract: We present a TCAD-based simulation framework established for quantum dot spin qubits in a silicon FinFET platform with all-electrical control of the spin state. The framework works down to 1 K and consists of a two-step simulation chain, from definition of the quantum dot confinement potential with DC bias voltages, to calculation of microwave response electric field at qubit locations using small-signal AC analysis. An average field polarization vector at each quantum dot is extracted via a post-processing step. We demonstrate functionality of this approach by simulation of a recently reported two-qubit device in the form of a 5-gate silicon FinFET. The impact of the number of holes in each quantum dot on the MW response E -field polarization direction is further investigated for this device. The framework is easily generalizable to study future multi-qubit large-scale systems. Highlights: TCAD simulation for hole spin qubit in Si FinFETs calculate microwave response E-field at qubit locations study impact of number of holes at dots